Preclinical disease activity in multiple sclerosis: A prospective study of cognitive performance prior to first symptom. Issue 4 (October 2016) - Cortese, Marianna; Riise, Trond; Bjørnevik, Kjetil; Bhan, Alok; Farbu, Elisabeth; Grytten, Nina; Hogenesch, Ineke; Midgard, Rune; Smith Simonsen, Cecilia; Telstad, Wenche; Ascherio, Alberto; Myhr, Kjell‐Morten
Abstract : Objective: To prospectively investigate potential signs of preclinical multiple sclerosis (MS) activity and when they are present prior to first symptom using data from a historical cohort. Methods: We linked the cognitive performance of all Norwegian men born 1950–1995 who underwent conscription examination at age 18 to 19 years to the Norwegian MS registry to identify those later developing MS, and randomly selected controls frequency‐matched on year of birth from the Norwegian Conscript Service database. In this nested case–control study, cognitive test scores were available for 924 male cases and 19, 530 male controls. We estimated mean score differences among cases and controls (Student t test) and the risk of developing MS comparing lower to higher scores (Cox regression) in strata of years to clinical onset. Results: Men developing first clinical MS symptoms up to 2 years after the examination scored significantly lower than controls (Δ = 0.80, p  = 0.0095), corresponding to a 6 intelligence quotient (IQ)‐point difference. Those scoring lowest, that is, >1 standard deviation below the controls' mean, had an increased MS risk during the 2 following years (relative risk = 2.81, 95% confidence interval = 1.52–5.20). Whereas results were similar for relapsing–remitting MS cases (RRMS), those developing primary–progressive MS (PPMS) scored a significant 4.6 to 6.9 IQ points lower than controls up to 20 years prior to first progressive symptoms. Interpretation: RRMS may start years prior to clinical presentation, and disease processes in PPMS could start decades prior to first apparent progressive symptoms. Cognitive problems could be present in both MS forms before apparent symptoms. Apart from potential implications for clinical practice and research, these findings challenge our thinking about the disease. Ann Neurol 2016;80:616–624